Laparoscopic intrapancreatic accessory splenectomy: A case report of recurrent immune thrombocytopenia in a 33 years old male patient after 6 years of splenectomy. (2019) - AlShammari, Abdullah; Kalagi, Dana; Hijji, Talal; Aburahmah, Mohammad
Highlights: Intrapancreatic Accessory Spleen (IPAS) is a rare embryological benign abnormality. (IPAS) should be considered in patients with recurrent immune thrombocytopenia (ITP). Although IPAS is a challenging diagnosis, it can be detected by the recent advancement of medical imaging. Abstract: Introduction: Intra-pancreatic Accessory Spleen (IPAS) is a rare benign abnormality of splenic embryology that should be considered in any patient with recurrence of immune thrombocytopenia (ITP). The case demonstrates that remission could be achieved if an IPAS is correctly identified and safely removed. Case presentation: We report a 33-years-old male patient who presented with chronic ITP relapsed 3 years post initial splenectomy. The patient presented with severe thrombocytopenia requiring steroids and intravenous immunoglobulin (IVIG). Discussion: IPAS can be identified using enhanced CT scan along with Tc-99 m sulfur colloid scintigraphy. Our patient underwent CT scan of abdomen and pelvis and was found to have an IPAS originating from the tail of the pancreas which was subsequently removed laparoscopically. The patient was then tapered off steroids and was followed up regularly and found to have acceptable platelet levels and no symptoms for 30 months post-surgery. Conclusion: The diagnosis of IPAS can be non-invasively made by an experienced radiologist with the recent advancement of medical imaging. Recognizing IPAS as a possible cause of ITP recurrence, and using minimally invasive approach can be performed safely and lead satisfactory outcomes.